PENULIS PEREMPUAN BERBICARA POLIGAMI DALAM TIGA NOVEL INDONESIA: KAJIAN GINOKRITIK (THE FEMALE WRITERS OF POLYGAMY SPEAKING IN THREE INDONESIAN NOVEL: GYNOCRITIC STUDY) - Ngatmiyatun, Ngatmiyatun (Universitas Lambung Mangkurat, 2024)
AbstractThe Female Writers of Polygamy Speaking in Three Indonesian Novel: Gynocritic Study. This study aims to understand the views of female writers in describing polygamy and to understand women's writing and women's culture as described by female writers through values, institutions, relationships, and communication between characters in the novel Wife Young, the novel Ibuku Malang Ibuku Kuyang and the novel Athirah. The approach used is a gynocritical approach with a qualitative descriptive method. The data in this study is in the form of text in the novel. The research results obtained (1) polygamy was carried out secretly, without permission from the first wife. (2) polygamy is done openly and with permission from the first wife. (3) polygamy is done secretly, the first wife is forced to give permission. Second, the writing of women and women's culture which is described by women writers through communication between characters in the three novels includes values, institutions, relationships, and methods of communication.Keywords: Female Writer, Polygamy, Novel, GynocriticAbstrakPenulis Perempuan Berbicara Poligami dalam Tiga Novel Indonesia: Kajian Ginokritik. Penelitian ini bertujuan untuk memahami pandangan penulis perempuan dalam menggambarkan poligami dan untuk memahami penulisan perempuan dan budaya perempuan yang digambarkan oleh penulis perempuan melalui nilai-nilai, institusi, hubungan-hubungan, dan komunikasi antar tokoh dalam novel Istri Muda, novel Ibuku Malang Ibuku Kuyang dan novel Athirah. Pendekatan yang digunakan yaitu pendekatan ginokritik dengan metode deskriptif kualitatif. Data dalam penelitian ini berupa teks pada novel. Hasil penelitian diperoleh (1) poligami dilakukan dengan sembunyi-sembunyi, tanpa ada izin dari istri pertama. (2) poligami dilakukan dengan terbuka dan ada izin dari istri pertama. (3) poligami dilakukan dengan sembunyi-sembunyi, istri pertama terpaksa memberikan izin. Kedua, Penulisan perempuan dan budaya perempuan yang digambarkan penulis perempuan melalui komunikasi antar tokoh pada ketiga novel meliputi, nilai, institusi, hubungan-hubungan, dan metode komunikasi.Kata Kunci: Penulis Perempuan, Poligami, Novel, Ginokritik